A year-round measurement of water-soluble trace and rare earth elements in arctic aerosol: Possible inorganic tracers of specific events - Turetta C.; Feltracco M.; Barbaro E.; Spolaor A.; Barbante C.; Gambaro A. (Atmosphere, 2021)
This study presents the year-round variability of the water-soluble fraction of trace elements (wsTE) and rare earth elements (wsREE) among size segregated airborne particulate matter samples collected at Ny-Å lesund in the Svalbard Archipelago from 26 February 2018 to 26 February 2019. Six different aerosol dimensional fractions were collected using a multi-stage Andersen impactor to better understand local and global circulation with the aim of disentangling the source of inorganic tracers from specific natural or anthropogenic sources. The wsTE and wsREE content, especially in the finest fractions in remote areas, is primarily related to long-range transport and it gives valuable information on (1) the global circulation, (2) the natural sources and (3) the contribution of human activities to aerosol composition. A Factor Analysis was applied to the dataset, including levoglucosan and methanesulfonic acid (MSA), to assess the possibility of using certain inorganic tracers as indicators of specific transport events or circulation regimes. We also investigate back-trajectories to determine potential source areas.